Modelo de gestión educativa fundamentado en la teoría del capital intangible expresado en la formación científica holística para incrementar el ingreso de los estudiantes egresados de educación secundaria matriculados en la academia preuniversitaria "kepler" a la Universidad Nacional de Trujillo, 2007 - Peláez Amado, José Wualter (2007)
The present work is an investigation directed to propose and apply a model of educational management that is essentially based on the management of the knowledge, the social, intellectual, cultural and moral capital; expressed in the holistic scientific education of the students who have finished their high schools for their revenue to the National University of Trujillo. The research has an experimental basic; the population was constituted by the pupils who study in the academy pre-university Kepler which was chosen aleatorelly among formally constituted seven academies in the region La Libertad, whose sample belongs to 3012 students registered in 6 academic corresponding to the year 2005, 2006, 2007. In the respective pictures the number of registered people in the academy is indicated, their scores obtained during their permanency, as well as the enrolled people and the students who approved the entrance exam for the university. In investigation it is concluded that the application of the model of educational management based on the intangible capital increases the revenue to the National University of Trujillo of the students who have finished their high schools and study at Kepler pre-university academic.